Surface Magnetism Correlation of Structural, Electronic and Chemical Properties with Magnetic Behavior - Getzlaff, Mathias; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
This volume reviews on selected aspects related to surface magnetism, a field of extraordinary interest during the last decade. The special emphasis is set to the correlation of structural, electronic and magnetic properties in rare earth metal systems and ferromagnetic transition metals. This is made possible by the combination of electron emission techniques (spin polarized photoelectron spectroscopy, magnetic dichroism in photoemission and spin polarized metastable deexcitation spectroscopy) and local probes with high lateral resolution down to the atomic scale (spin polarized scanning tunneling microscopy / spectroscopy).
Experimental Aspects -- Structural and Electronic Properties of Rare Earth Metal Systems -- Influence of Adsorbates -- Magnetic Characterization -- Summary.
Keywords: Materials; Surfaces (Physics).; Materials Science; Surfaces and Interfaces, Thin Films; Metallic Materials; Atomic, Molecular, Optical and Plasma Physics